2015
DOI: 10.1007/8904_2015_444
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Mutations in the First Swedish Patient with Purine Nucleoside Phosphorylase Deficiency and Clinical Outcome After Hematopoietic Stem Cell Transplantation with HLA-Matched Unrelated Donor

Abstract: Purine nucleoside phosphorylase (PNP) is an enzyme active in the purine salvage pathway. PNP deficiency caused by autosomal recessive mutations in the PNP gene leads to severe combined immunodeficiency (SCID) and in two thirds of cases also to neurological effects such as developmental delay, ataxia, and motor impairment.PNP deficiency has a poor outcome, and the only curative treatment is allogenic hematopoietic stem cell transplantation (HSCT). We present the first Swedish patient with PNP deficiency with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The immune dysregulation associated with PNP deficiency also leads to autoimmunity, resulting in hematological cytopenia and frequent malignant transformation (10,11). Non-infectious dysfunction, particularly neurological abnormalities such as ataxia and spasticity, are frequently reported in PNP-deficient patients (12) and in mice lacking the PNP enzyme (13). These anomalies could be due to the ubiquitous nature of the PNP enzyme and the diverse biological roles of PNP and purine metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune dysregulation associated with PNP deficiency also leads to autoimmunity, resulting in hematological cytopenia and frequent malignant transformation (10,11). Non-infectious dysfunction, particularly neurological abnormalities such as ataxia and spasticity, are frequently reported in PNP-deficient patients (12) and in mice lacking the PNP enzyme (13). These anomalies could be due to the ubiquitous nature of the PNP enzyme and the diverse biological roles of PNP and purine metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell (HSC) transplantations can correct the immune deficiency and possibly halt or even improve the neurological deficits. However, transplant-related complications are still frequent and typical (normal) development is not always achieved, possibly because of incomplete donor chimerism that limits the ability of PNP-proficient hematopoietic cells to restore purine metabolism ( 8 , 12 , 17 21 ). Moreover, even when donor chimerism is achieved, neurological deficits might persist.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, this is the first reported patient with PNP deficiency detected with this approach; while other cases have been reported using TMS [8]. While other studies performed retrospectively after the genetic diagnosis showed reduced TREC in DBS and in whole blood DNA extraction [14], this was not the case in the publication by Brodszki N et al [15], showing than PNP deficiency should be suspected with compatible clinical features, even in NBS with TRECS that yielded normal results. Previous reports have cited TMS on DBS as an accurate approach for this purpose [1,2,14,16].…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Baguette et al ( 9 ) reported that developmental retardation was permanent in a patient with PNP deficiency despite successful HSCT. In contrast to these patients, Brodszki et al ( 10 ) emphasized that their 2-year-old patient who underwent HSCT showed very successful improvements both immunologically and neurologically; the level of fine motor skills reached to 3–4 years of age when the patient was aged 55 months, and the speech, social and emotional skills also reached the same age levels. Only one of our patients had the chance of undergoing HSCT but was lost because of a complication of veno-occlusive disease.…”
Section: Discussionmentioning
confidence: 98%